2014
DOI: 10.1073/pnas.1404978111
|View full text |Cite
|
Sign up to set email alerts
|

Combining linkage and association mapping identifiesRECEPTOR-LIKE PROTEIN KINASE1as an essentialArabidopsisshoot regeneration gene

Abstract: De novo shoot organogenesis (i.e., the regeneration of shoots on nonmeristematic tissue) is widely applied in plant biotechnology. However, the capacity to regenerate shoots varies highly among plant species and cultivars, and the factors underlying it are still poorly understood. Here, we evaluated the shoot regeneration capacity of 88 Arabidopsis thaliana accessions and found that the process is blocked at different stages in different accessions. We show that the variation in regeneration capacity between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 58 publications
(69 reference statements)
1
64
1
Order By: Relevance
“…Even in the same species, the shoot regeneration capacity varies among different 77 genotypes (Motte et al, 2014). However, the mechanisms underlying this natural variation in shoot 78 regeneration capacity remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the same species, the shoot regeneration capacity varies among different 77 genotypes (Motte et al, 2014). However, the mechanisms underlying this natural variation in shoot 78 regeneration capacity remains unclear.…”
mentioning
confidence: 99%
“…Several studies have identified a few quantitative trait loci 79 related to natural variations in shoot regeneration (Schiantarelli et al, 2001;Lall et al, 2004;80 Velázquez et al, 2004). A recent study has shown that RECEPTOR-LIKE PROTEIN KINASE1 81 (RPK1) gene is involved in natural variation in shoot regeneration capacity (Motte et al, 2014).…”
mentioning
confidence: 99%
“…It is only very recently that the complex shoot regeneration process has been dissected into phases, and the links between them examined. A recent report by Motte et al [34] observed wide natural variation in different parameters such as callus development, callus greening, formation of primordia, and shoots during shoot regeneration across 88 Arabidopsis accessions. They performed correlation analysis between the traits.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variability has been utilized to identify novel factors that modulate the efficiency of regeneration in many plant species (Armstrong et al, 1992;Taguchi-Shiobara et al, 1997;Ben Amer et al, 1997;Flores Berrios et al, 2000;Mano and Komatsuda, 2002;Trujillo-Moya et al, 2011). A leucine-rich repeat receptor-like kinase, RECEPTOR-LIKE PROTEIN KINASE1 (RPK1), for instance, was identified as a major quantitative trait locus (QTL) that affects shoot regeneration in Arabidopsis accessions (Motte et al, 2014). RPK1 is implicated in ABA signaling, and although this hormone has not been studied extensively in the context of regeneration it has been reported to influence shoot regeneration in several plant species (Ghasemi Bezdi et al, 2007;Hoang and Raldugina, 2012;Huang et al, 2012).…”
Section: Natural Variations That Impact Plant Regenerationmentioning
confidence: 99%